Perspektif Hukum dan Ekonomi atas Kerjasama Luar Negeri oleh Pemerintah Daerah - Rumengan, Jemmy (UI Scholars Hub, 2009)
Globalization and the increase of international relations have created new actors in international community. States are no longer the only parties in international relations, nowadays local government (city/province) has become one of the actors in international relations. In this context, law has an important role to regulate the relations between local government in a state with another local government in other state. It takes national and international law to arrange that international interaction or relations. In economic perspective, international relations by local government should give a real contribution to their local community and for their state. That’s why international relations by local government can be seen from law perspective and also from economic perspective.